2009
DOI: 10.1175/2008mwr2561.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Data Assimilation on Forecasting Convection over the United Kingdom Using a High-Resolution Version of the Met Office Unified Model

Abstract: A high-resolution data assimilation system has been implemented and tested within a 4-km grid length version of the Met Office Unified Model (UM). A variational analysis scheme is used to correct larger scales using conventional observation types. The system uses two nudging procedures to assimilate high-resolution information: radar-derived surface precipitation rates are assimilated via latent heat nudging (LHN), while cloud nudging (CN) is used to assimilate moisture fields derived from satellite, radar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 35 publications
0
79
0
Order By: Relevance
“…The most common method in operational use at the time of writing is latent heat nudging (LHN: Jones and Macpherson, 1997;Leuenberger, 2005;Leuenberger and Rossa, 2007;Montmerle et al, 2007;Stephan et al, 2008;Dixon et al, 2009), although a variety of more advanced techniques have been studied in research contexts. Operational experience suggests that the impact of the assimilated radar data is often short-lived, e.g.…”
Section: Radar Data Assimilation: One Avenue To Improving Srnwp Qpfmentioning
confidence: 99%
“…The most common method in operational use at the time of writing is latent heat nudging (LHN: Jones and Macpherson, 1997;Leuenberger, 2005;Leuenberger and Rossa, 2007;Montmerle et al, 2007;Stephan et al, 2008;Dixon et al, 2009), although a variety of more advanced techniques have been studied in research contexts. Operational experience suggests that the impact of the assimilated radar data is often short-lived, e.g.…”
Section: Radar Data Assimilation: One Avenue To Improving Srnwp Qpfmentioning
confidence: 99%
“…Therefore, the nudging method is still used to assimilate radar reflectivity data among other observations (e.g. Sokol andRezacova, 2006, 2009;Stephan et al, 2008;Dixon et al, 2009). The application of the nudging was also supported by our focus on the very short-range precipitation forecast because the time consumption of the 4D-Var and PF methods restricts their operational application for very short lead times.…”
Section: Introductionmentioning
confidence: 93%
“…The most common method in operational use at the time of writing is latent heat nudging (LHN: Jones and Macpherson, 1997;Leuenberger, 2005;Leuenberger and Rossa, 2007;Stephan et al, 2008;Dixon et al, 2009), although a variety of more advanced techniques have been studied in research contexts (e.g. Jakubiak, 2008;Caumont et al, 2009).…”
Section: Radar Data Assimilation As Promising Avenue For Improved Shomentioning
confidence: 99%
“…For example, Stephan et al (2008) show a case study where assimilation of radar data continued to have a strong positive impact after 6 h of free forecast, but commented that this was 'one of the most successful cases with regard to the duration of forecast impact of LHN' within their 2-month trial period. Ducrocq et al (2002), Leuenberger (2005) and Dixon et al (2009), on the other hand, reported on several convective cases in which the data assimilation has a dramatic impact on skill during both the assimilation and subsequent forecast periods on nowcasting time scales. The fact that the impact of the radar data normally decreased rapidly in the first 4 h of the free forecast is likely to be linked to the short predictability of cumulus convection, an inappropriate representation of the convective environment, as well as to deficiencies in current data assimilation methods.…”
Section: Radar Data Assimilation As Promising Avenue For Improved Shomentioning
confidence: 99%